PENGARUH PEMBELAJARAN PENDIDIKAN AL- QUR’AN TERHADAP KARAKTER ANAK SISWA KELAS VII SMPIT AR RISALAH SUKOHARJO TAHUN AJARAN 2022/2023 - Kinasih, Pertiwi; Amin, Lailla Hidayatul; Sulistyowati, Sulistyowati (UMSU, 2024)
This study aims to: 1) Understand the implementation of Al-Qur’an education at SMPIT Ar Risalah Laweyan, Sukoharjo, during the 2023/2024 Academic Year; 2) Identify the character of seventh-grade students at SMP IT Ar Risalah Laweyan, Sukoharjo, during the 2023/2024 Academic Year; and 3) Analyze the influence of Al-Qur’an education on the character of seventh-grade students at SMP IT Ar Risalah Laweyan, Sukoharjo. This research employs a quantitative approach with a correlational method. The subjects of the study are seventh-grade students, with additional information sourced from Al-Qur’an teachers and students. Data were collected using questionnaires, interviews, observations, and documentation. Data analysis includes data collection, data reduction, respondent data analysis, and conclusion drawing. The findings reveal that Al-Qur’an education at SMP IT Ar Risalah has been implemented through planning, execution, and evaluation phases to shape students’ character. In the planning phase, the school’s vision and mission serve as guidelines for Al-Qur’an education, supported by a strong commitment to Islamic values-based education. The execution phase systematically integrates the Al-Qur’an education-based curriculum. Meanwhile, the evaluation phase is conducted transparently, accountably, efficiently, and effectively to improve the quality of education. This study concludes that Al-Qur’an education significantly contributes to shaping students' character, creating a conducive learning environment aligned with Islamic educational values.